1984
DOI: 10.1215/03616878-9-3-515
|View full text |Cite
|
Sign up to set email alerts
|

Method of Payment and the Cesarean Birth Rate in a Hospital in Northeast Brazil

Abstract: This paper examines factors associated with the cesarean birth rate, including medical condition and method of payment, in the largest maternity hospital of Fortaleza, Brazil. Data were collected on 5996 women who delivered at the Maternidade Escola Assis Chateaubriand from October 1980 to July 1981. All women were classified according to how they paid for their care: private (financed at least part of their care with own funds), insured (federal or state), or indigent. Private patients were found to be far mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Outros estudos evidenciaram altas taxas em todas as regiões brasileiras, com predomí-nio nas mais desenvolvidas 4 e maiores taxas no setor privado -onde o risco clínico esperado seria menor - P<0,001*** Valor de p calculado pelo método da razão de verossimilhança *Modelo ajustado inclui escolaridade e idade maternas, duração da gestação e macro-regional **Modelo ajustado inclui macro-regional de saúde, escolaridade e idade maternas, duração da gestação e etnia/cor do recém-nascido (somente 1998 e 2000) ***Modelo ajustado inclui macro-regional, escolaridade e idade maternas, duração da gestação e consulta pré-natal do que no público. 2,8,14 Taxas mais altas também foram descritas nas regiões Norte e Nordeste, onde também ocorreram altas taxas de ligadura tubárea em hospitais privados. 8,13 Esses resultados sugerem que o excesso de cesarianas é um problema de saúde pú-blica que ultrapassa a fronteira das questões meramente clínicas.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Outros estudos evidenciaram altas taxas em todas as regiões brasileiras, com predomí-nio nas mais desenvolvidas 4 e maiores taxas no setor privado -onde o risco clínico esperado seria menor - P<0,001*** Valor de p calculado pelo método da razão de verossimilhança *Modelo ajustado inclui escolaridade e idade maternas, duração da gestação e macro-regional **Modelo ajustado inclui macro-regional de saúde, escolaridade e idade maternas, duração da gestação e etnia/cor do recém-nascido (somente 1998 e 2000) ***Modelo ajustado inclui macro-regional, escolaridade e idade maternas, duração da gestação e consulta pré-natal do que no público. 2,8,14 Taxas mais altas também foram descritas nas regiões Norte e Nordeste, onde também ocorreram altas taxas de ligadura tubárea em hospitais privados. 8,13 Esses resultados sugerem que o excesso de cesarianas é um problema de saúde pú-blica que ultrapassa a fronteira das questões meramente clínicas.…”
Section: Discussionunclassified
“…2,8,14 Taxas mais altas também foram descritas nas regiões Norte e Nordeste, onde também ocorreram altas taxas de ligadura tubárea em hospitais privados. 8,13 Esses resultados sugerem que o excesso de cesarianas é um problema de saúde pú-blica que ultrapassa a fronteira das questões meramente clínicas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Here and abroad, most studies have found that rich women have higher C-section rates than poor women. For example, the rates for women with government insurance in Italy (Bertollini et al 1992) and in Brazil (Janowitz et al 1984) were much lower than for presumably richer private patients, even after adjustment for age and parity. Hospitals in wealthy suburbs of the United States are often marked by very high C-section rates (Van Tuinen and Wolfe 1992).…”
Section: Other Costs To Mothersmentioning
confidence: 95%